Dutch research into the country house and its landscape: Current state of scholarship and outlook (Bulletin KNOB, 2021)
One of the unmistakable trends in current country house research is the growing interest in the landscape context of country houses. The unquestioned emphasis on the main house and the garden is increasingly giving way to an approach that includes or focuses on the wider setting: village, nature, town, infrastructure, farms, churches, and other country houses. This article sketches the rise of this approach and offers an overview of the various perspectives. Among the aspects covered by landscape studies are country house regions, choice of location, the productive landscape, infrastructure, the political landscape and the mental landscape. Although this growing interest in the landscape setting is one of the most important recent developments in country house research, most of these studies are predominantly descriptive. This article calls for the establishment of a firmer methodological and theoretical underpinning – a task to which it is to be hoped that future researchers will devote themselves.